2021
DOI: 10.1002/jca.21875
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of therapeutic plasma exchange in patients with Crimean‐Congo hemorrhagic fever

Abstract: Objective To examine the efficacy of therapeutic plasma exchange (TPE) in patients critically ill with Crimean‐Congo hemorrhagic fever (CCHF). Methods Patients with CCHF received supportive treatment (ST) or TPE. After laboratory and clinical evaluations, the patients were divided into mild, moderate, and severe CCHF groups according to the severity score index (SSI). To assess the efficacy of TPE, the incubation period, time of admission to hospital, hospitalization duration, mortality rate and times to recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Table 1 shows the study type, methods, outcomes, and the country of the studies that analyzed the use of plasma exchange for the treatment of CCHF [13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1 shows the study type, methods, outcomes, and the country of the studies that analyzed the use of plasma exchange for the treatment of CCHF [13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that the mortality rate was lower in the TPE group than in the ST group, but the duration of hospitalization and the time to platelet recovery were longer in the TPE group. In patients with intermediate severity, the TPE was not helpful; however, it might be useful in a severe disease presentation [ 13 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations